Optimum design and sizing of photovoltaic panels in off-grid photovoltaic system for rural residential area - Low, Raymond (2022)
Global energy consumption increases rapidly due to population growth, improvements in living standard and infrastructure and advancement in harnessing energy. Malaysia is one of the countries that has the advantage in generating electricity from solar energy due to its location in the equatorial zone. The electricity supply status for many rural areas and small towns in the Malaysia especially at East Malaysia is still insufficient. Utility company has the difficultly to supply a reliable power source to the remote area due to its topography and distance from the grid. Therefore, off-grid photovoltaic (PV) system or standalone PV system has become the best solution for those area far from the network grid. However, the electricity generated from the standalone PV system varies due to changing weather condition. Thus, battery energy storage system is needed to be installed and integrated with a standalone PV system to meet the demand of electricity during low irradiation days and nighttime. But high operational cost of the battery causes people less interest on investing the battery energy storage system. It is important to design an appropriate size of the PV array and battery capacity to reduce operational cost of battery. In the past, most of the researched or industrial designs focus on optimizing the battery capacity based on the number of autonomy days required for the standalone PV system. Few researchers address the importance of how iii fast a PV array can fully charge a battery bank to handle another subsequent long raining day after first one. In this research project, different k values and number of autonomy days were used to determine the suitable size of a PV array. k in this project defined as PV size where it means that different k value represents different PV size. k is defined as the number of days required for a PV array to fully charge a battery bank under over discharge protection state, in other words, the battery bank has reached its depth of discharge capacity after supplying electricity for the pre-designed number of autonomy days. Different k values represents different PV sizes. k in this project is simply called as charging speed. k=4,3.5,3,2.5,2 and 1.5 were used in the simulation of the appropriate size of PV panels to yield a reliable electricity supply for a period of year. An appropriate k values determine based on the criteria that the subsequent electricity been charged to a battery that just reached its over discharge protection mode, can cover energy demand of another subsequent continuously rainy days. There are two study cases were studied to determine appropriate k values for reliable supply of 2 or 3 autonomy days. The results conclude that charging speed (k) =1.5 and 2.5 are suitable for a PV capacity required to support the electricity demand for 2 and 3 autonomy days respectively. In conclusion, the required minimal charging speed (k) and PV capacity in the optimization of the PV system was determined.